Pelestarian Nilai-Nilai Spiritual Nelayan Pattorani Galesong Melalui Gerakan Hilirisasi Budaya dan Ormawa Sejarah UNM - Khaerunnisa, Khaerunnisa; Subair, Ahmad; Susetya, Agil; Rafly, Muh.; Tenritata, Andi Aso (CV. Ulil Albab Corp, 2024)
Program